2013 IEEE Global Engineering Education Conference (EDUCON) 2013
DOI: 10.1109/educon.2013.6530276
|View full text |Cite
|
Sign up to set email alerts
|

Using flowchart-based programming environments for simplifying programming and software engineering processes

Abstract: Programming environments based on an iconic, flowchart-based notation have been widely used in the context of introducing novices to programming. These tools were initially heavily based on the technology of structure editing, with the aim of alleviating the burden of focusing on the syntactic details of programming languages and giving the chance to focus on acquiring problem solving skills. The technology of program animation was also utilized, in order to allow for a better comprehension of programming stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…These environments offer a number of advantages such as object oriented programming, running through the program automatically, synchronized execution of flowchart and corresponding source code, explanatory visualization, and even web based applications and collaborative activities [13]. But, as mentioned before, the main aim is facilitating the understanding of algorithmic concepts.…”
Section: Grp Environments For Implementing Sfcsmentioning
confidence: 99%
“…These environments offer a number of advantages such as object oriented programming, running through the program automatically, synchronized execution of flowchart and corresponding source code, explanatory visualization, and even web based applications and collaborative activities [13]. But, as mentioned before, the main aim is facilitating the understanding of algorithmic concepts.…”
Section: Grp Environments For Implementing Sfcsmentioning
confidence: 99%
“…In the visual programming described in the article by Charntaweekhun and Wangsiripitak [ 1 ], students learning programming can simply compile and run a program using the FCh without any coding and allow for easy debugging and detection. Thus, the presented system is excellent for teaching structural programming, as it avoids the learning difficulty caused by the individual syntax of programming languages, thus providing an opportunity to develop problem-solving skills [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, Xinogalos [ 5 ] provides an overview of FCh-based programming environments and makes suggestions for making software engineering education more effective. In the article in Cabo [ 6 ], it was found that students who use FCh to solve problems effectively will learn Python or similar programming languages more easily (r-squared = 0.68).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be characterized, or at least explained, in terms of the conceptual modeling languages that reflect its core concepts and that encourage developers to adhere to its principles. For example, Flow Charts and Control-Flow Diagrams can be used to teach someone to think according to the Procedural Programming (PP) paradigm [2], whereas UML Class, Interaction, and State Diagrams can help someone understand Object-Oriented Programming (OOP) [3].…”
Section: Introductionmentioning
confidence: 99%